Avifaunal Diversity of Gudavi Bird Sanctuary, Sorab, Shimoga, Karnataka - Dayananda, G.Y. (Our Nature, 2010)
Two hundred and seventeen species of birds belonging to 48 families were recorded in the three year study at the Gudavi sanctuary, Sorab, Shimoga district, Karnataka. Most of the families were represented by less than thirteen species except for Muscicapidae (35 species). These include 160 residents, 46 resident migratory and 11 migratory birds. 54 species of water dependent birds were recorded from the wetlands of the sanctuary. Among the birds recorded in this study, about 45.62% are insectivores and other dominating types include piscivores (12.44%), omnivores (11.98%), frugivores (9.67%), grainivores (8.75%), carnivores (7.83%) and nectarivores (3.68%) respectively. Key words: Avifauna, Biodiversity, Gudavi Bird Sanctuary, Sorab DOI: 10.3126/on.v7i1.2556 Our Nature (2009) 7:100-109